MINAT INVESTASI MELALUI KEPUTUSAN INVESTASI SEBAGAI VARIABEL INTERVENING (Studi pada Nasabah PT. Pegadaian Kota Rembang) - Pratiwi, Mita Anggi; Sumastuti, Efriyani; Indriasari, Ika (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine and analyze Investment Knowledge, Investment Risk, and Demographics on Investment Interest through Investment Decisions as an Intervening Variable study on Customers of PT Pegadaian Kota Rembang. The population in this study were 100 respondents with non-probability sampling technique using saturated sampling where all members of the population were sampled. Data processing techniques using the Smart PLS application. Based on research on customers of PT Pegadaian Kota Rembang, the research results obtained are knowledge has a significant effect on investment decisions. Risk has a negative and significant effect on investment decisions. Demographics have a positive and significant effect on investment decisions. Knowledge has a significant influence on investment interest. There is no effect of risk on investment interest. Demographics have a significant effect on investment interest. The decision to investment interest has a positive effect.